OPTIMIZATION OF THE FORMULATION PARAMETERS OF A PARAPHARMACEUTICAL 100% BIO CREAM - Safia, Djedri; Ahmed, Boucherit; Zohra, Boumdal; Rachid, Issaadi (MATTER: International Journal of Science and Technology, 2017)
The extraction of the aromatic fraction (hydrolat, essential oil) fresh aerial part of Lavandula vera was accomplished by steam distillation. The average yield of essential oil is 1-2%. The anti-inflammatory cream BIO obtained has interesting dermal properties. This cream is endowed with remarkable healing properties and anti-infectious. It leads to dermatological applications and opens the way eventually fruitful research. During this work we have formulated an anti-inflammatory cream 100% BIO whose active ingredient is the essential oil of lavender with these attractive properties. Optimization of formulation parameters made it possible to have a stable cream. Physicochemical analysis, sensory (with diagram properties evaluation) and comparative study with a reference cream (conventional) was able to show the qualities of our BIO cream.